2019
DOI: 10.1590/1414-431x20198273
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effects of Uncaria rhynchophylla alkaloid extract on LPS-induced preeclampsia symptoms and inflammation in a pregnant rat model

Abstract: Excessive pro-inflammatory cytokines result in adverse pregnancy outcomes, including preeclampsia-like phenotypes, and fetal growth restriction. Anti-inflammation might be an effective therapy. The aim of this research was to investigate whether Uncaria rhynchophylla alkaloid extract (URE), a highly safe anti-inflammation constituent of the herb, can inhibit inflammation and improve clinical characteristics of preeclampsia in a lipopolysaccharide (LPS)-induced preeclampsia rat model. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…Recent reports indicated that PE/HDP is also induced by lipopolysaccharide (LPS) [32] and that RAGE mediates LPS signaling and acts as an LPS receptor [33,34,35,36,37,38]. Thus, we tested whether LPS up-regulate gene expression of IL-6 and CCL2 in human SW872 adipocytes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports indicated that PE/HDP is also induced by lipopolysaccharide (LPS) [32] and that RAGE mediates LPS signaling and acts as an LPS receptor [33,34,35,36,37,38]. Thus, we tested whether LPS up-regulate gene expression of IL-6 and CCL2 in human SW872 adipocytes.…”
Section: Resultsmentioning
confidence: 99%
“…As most but not all the ligands for RAGE up-regulate (pro)inflammatory mediators, such as IL-6 and CCL2, some other RAGE ligands such as macrophage-1 antigen/cluster of differentiation molecule 11b [54], amyloid β peptide [55], β-sheet fibrils [56], advanced oxidation protein products [57], complement C3a [58], LPS [33], and phosphatidylserine on the surface of apoptotic cells [59] might increase the expression of IL-6 and CCL2, leading to PE/HDP in pregnant women. In fact, recent reports showed that PE/HDP was also induced by LPS [32], and that RAGE mediated LPS signaling and acted as an LPS receptor [33,34,35,36,37,38]. Thus, we tested whether LPS up-regulate gene expression of IL-6 and CCL2 in human SW872 adipocytes, and found that LPS significantly up-regulated the expression of IL-6 and CCL2 in SW872 cells via RAGE (Figure 6, Figure 7, Figure 8 and Figure 9).…”
Section: Discussionmentioning
confidence: 99%
“…Butyric acid was reported to down-regulate LPS-induced inflammation by modulating the function of macrophages and inhibiting histone deacetylation [35][36][37][38]. In addition, LPS may induce Toll-like receptor 4-mediated immune inflammation responses and was related to PE pathogenesis [39]. Notably, although the significance of the decrease in butyric acid was reduced after excluding the patients with comorbidities in the present study, the trend of reduction in patients with PE was retained, suggesting that decreased faecal butyric acid levels might contribute to PE development through an LPS-related mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…21 As an antiin ammatory constituent of the herb, uncaria rhynchophylla can suppress in ammation and mitigating preeclampsia-like symptoms in a rat model. 22 There is some evidence suggesting that in addition to anticoagulation, the potential effects of low molecular weight heparin in preventing preeclampsia progress are mediated by suppressing in ammation. 23 The cholinergic anti-in ammatory pathway (CAP) bridges the immune and nervous systems 9 and plays multi-effect roles in modulating in ammation.…”
Section: Discussionmentioning
confidence: 99%